KOMUNIKASI DALAM KEGIATAN MARESEK UNTUK MEMPERSIAPKAN ADAT PERNIKAHAN MINANG (Etnografi Komunikasi Tradisi Maresek Adat Minang Bukittinggi Nagari Salo) - Nabila Ardillah; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The research was carried out in the village of Agam Regency Meatball sub Salo. The reason researchers take at the village and subdistrict Baso Kabuaten Salo, Agam, West Sumatra Province because of the community in the village of Salo still uses the maresek customs, in order to maintain the tradition of hereditary and cultural heritage. This research aims to understand the communicative situation in the tradition of the indigenous maresek minang village Salo, Baso, Agam Regency, to describe the communicative event in the tradition of the indigenous maresek minang village Salo, Baso, County Agam, to describe the communicative acts in the tradition of the indigenous maresek Minang village Salo, Kecamatn Baso, Agam Regency. Based on the results of the above study obtained from the field during the placing of the research, then the author will discuss overall regarding the "indigenous traditions of communication pemolaan maresek Minang didesa Salo Agam by using method qualitative ethnographic pendekatakan with communication. Discussion of the results of the research is meant to show the research analysis based on the results of the peneltian and refers to a theoretical grounding is used. In the Ethnography of communication discussion "pemolaan communication maresek indigenous community trades minang didesa Salo Agam, based on the results of the research that has been described in previous chapters, and is based on data obtained in field, then the researchers draw conclusions from the discussion and give you some advice and input that can be useful as an effort to help preserve and maintain the indigenous maresek.Keywords: Communication, Maresek, Marriage Customs Minang